Immune Mediated Sub-Epithelial Blistering Disorders: Case Series - LM, ABHINAYA; ARVIND, MUTHUKRISHNAN (The journal of contemporary issues in business and government, 2020)
Subepithelial vesiculobullous conditions are chronic autoimmune disorders that arise from reactions directed against components of the hemidesmosomes or basement membrane zones (BMZ) of stratified squamous epithelium to which the term immune-mediated subepithelial blistering diseases (IMSEBD) has been given.Subepithelial vesiculobullous disorders present as blisters and erosions, and diagnosis are confirmed by biopsy examination with immunostaining.The sub epithelial disorders include Mucous membrane pemphigoid,Angina bullosa haemorrhagica,Linear IgA disease,Bullous pemphigoid,Erythema multiforme.These disorders post a challenge to the oral physician due to clinical and histological severity in a variety of disorders.Early diagnosis and appropriate treatment for oral lesions can possibly prevent further cutaneous involvement as in 70% of cases oral lesions precede to that of cutaneous lesions.Accurate and definitive diagnosis is done by immunofluorescence, direct and indirect.This article comprises of case series of immune mediated subepithelial blistering disorders.